Analisis Perbandingan Kinerja Keuangan Perusahaan Farmasi Milik Pemerintah (BUMN) Dengan Perusahaan Farmasi Swasta di Bursa Efek Indonesia (Periode 2013-2017) - Aida Nahar; Erlinda Dyah Evisa (Accounting Study Program, Faculty of Economics and Business, 2018)
The financial performance of a company can be interpreted as a good prospect or future, growth and development potential for the company. This study aims to analyze the comparison of financial performance between government-owned pharmaceutical companies (BUMN) and private pharmaceutical companies listed on the Indonesia Stock Exchange from 2013-2017. The variables used to compare are profitability ratios (GPM, NPM, OPM, ROA, ROI, and ROE). The research population is all pharmaceutical companies listed on the IDX. The sampling method is saturated sample. The number of samples is 6 government-owned pharmaceutical companies and 2 private pharmaceutical companies. The data collection method is by recording financial statement documents and data analysis using the Independent sample T-test. The results showed that there were differences in financial performance between government-owned pharmaceutical companies (BUMN) and private pharmaceutical companies. This is because each variable produces a profitability value greater than = 0.05. Private Pharmaceutical Companies can develop and maintain what has been achieved and State Owned Pharmaceutical companies should give the government freedom of management for company management, so that companies develop their products, not only domestically but also abroad.